On the Fragmentation in Literature - Natalia N. Smirnova (Studia Litterarum)
The aim of this article is to outline the ways to research fragmentation in literature. It raises the following problems, relevant for literary theory: a) each period has different understanding of what is a whole and what is a fragment; b) ideas about the essence and the meaning of fragmentary forms (including the views on increasing / decreasing complexity in literature) are also different; c) the special logic of fragmentation as a technique emerges only in the era of authorship (as opposed to traditionalism), i.e. the individual vision, or the author’s view that destroys the canon. The problem of fragmentation is fundamental for our understanding of the perception and construction of the text, since in different historical periods, the concept of the fragment being contingent on tradition, reread and reinvented in different ways, is in continuous dialogue with its time. The essay concludes that what is considered to be the whole in one historical period turns out to be a fragment in the other, and vice versa.